The Effect Of Soaking Time And Seed Location In The Fruit On The Growth Of Papaya Seedlings - Wijaya, Wijaya; Dukat, Dukat; Jannah, Nurul (Ann Publisher, 2025)
This study aims to determine the effect of a combination of soaking time and seed location in the fruit on the early growth of California papaya cultivar plants. The study used an experimental method, the experiment was carried out in the Arjawinangun area, Cirebon Regency, from March to June 2023. Based on the results of the study on the effect of soaking time and seed location in the fruit on the growth of California papaya cultivar seedlings, the following conclusions can be drawn: the difference in the combination of soaking time and seed location in the fruit gives a difference to the initial growth variables, and good early growth of papaya plants is obtained from the combination of 24-hour soaking time and seed location at the base.